Emotions and Narrative in Ancient Literature and Beyond : Studies in Honour of Irene de Jong - Berg, Baukje van den; Bakker, Mathieu P. de; Klooster, Jacqueline (Mnemosyne, Supplements, 2022)
Emotions are at the core of much ancient literature, from Achilles' heartfelt anger in Homer's Iliad to the pangs of love of Virgil's Dido. This volume applies a narratological approach to emotions in a wide range of texts and genres. It seeks to analyze ways in which emotions such as anger, fear, pity, joy, love and sadness are portrayed. Furthermore, using recent insights from affective narratology, it studies ways in which ancient narratives evoke emotions in their readers. The volume is dedicated to Irene de Jong for her groundbreaking research into the narratology of ancient literature.